Percutaneous Transforaminal Endoscopic Discectomy Versus Microendoscopic Discectomy for Lumbar Disk Herniation: Five-year Results of a Randomized Controlled Trial. Issue 2 (15th January 2023) - Chen, Zihao; Zhang, Liangming; Dong, Jianwen; Xie, Peigen; Liu, Bin; Chen, Ruiqiang; Li, Shangfu; Liu, Zhongyu; Yang, Bu; Feng, Feng; He, Lei; Yang, Yang; et al.
Abstract : Study Design: A prospective randomized controlled study. Objective: To compare the efficacy and safety between percutaneous transforaminal endoscopic discectomy (PTED) and microendoscopic discectomy (MED). Summary of Background Data: Two kinds of minimally invasive discectomy, PTED and MED, are now widely used for treating lumbar disk herniation (LDH). The long-term comparative results of these two techniques still remained uncertain. Materials and Methods: In this single-center, open-label, randomized controlled trial, patients were included if they had persistent signs and symptoms of radiculopathy with corresponding imaging-confirmed LDH and were randomly allocated to PTED or MED groups. The primary outcome was the score of Oswestry Disability Index (ODI) and the secondary outcomes included the score of Medical Outcomes Study 36-Item Short-Form Health Survey bodily pain (SF36-BP) and physical function (SF36-PF), European Quality of Life—Five Dimensions (EQ-5D), Visual Analog Scales for back pain (VAS-back) and leg pain (VAS-leg). Results: A total of 241 patients were accepted to enroll in our randomized controlled trial, of which 119 were randomly assigned to the PTED group, and the rest 122 were assigned to the MED group. A total of 194 out of 241 patients (80.5%) completed the five-year follow-up. PTED group was associated with shorter postoperative in-bed time and length of hospital stay. Both primary and secondary outcomes did not differ significantly between the two treatment groups at each follow-up time point. During the five-year follow-up, seven recurrent cases occurred in PTED and MED groups, respectively. Conclusion: Over the five-year follow-up period, PTED and MED were both efficacious in the treatment of LDH. The long-term clinical outcomes and recurrent rates were comparable between the treatment groups. PTED represents a more minimally invasive technique with the advantages of rapid recovery.